3D image‐guided robotic needle positioning system for small animal interventions. Issue 1 (4th January 2013) - Bax, Jeffrey S.; Waring, Christopher S. R.; Sherebrin, Shi; Stapleton, Shawn; Hudson, Thomas J.; Jaffray, David A.; Lacefield, James C.; Fenster, Aaron
Abstract : Purpose: : This paper presents the design of a micro‐CT guided small animal robotic needle positioning system. In order to simplify the robotic design and maintain a small targeting error, a novel implementation of the remote center of motion is used in the system. The system has been developed with the objective of achieving a mean targeting error of <200 μm while maintaining a high degree of user friendliness. Methods: : The robot is compact enough to operate within a 25 cm diameter micro‐CT bore. Small animals can be imaged and an intervention performed without the need to transport the animal from one workspace to another. Not requiring transport of the animal reduces opportunities for targets to shift from their localized position in the image and simplifies the workflow of interventions. An improved method of needle calibration is presented that better characterizes the calibration using the position of the needle tip in photographs rather than the needle axis. A calibration fixture was also introduced, which dramatically reduces the time requirements of calibration while maintaining calibration accuracy. Two registration modes have been developed to correspond the robot coordinate system with the coordinate system of the micro‐CT scanner. The two registration modes offer a balance between the time required to complete a registration and the overall registration accuracy. The development of slow high accuracy and fast low accuracy registration modes provides users with a degree of flexibility in selecting a registration mode best suited for their application. Results: : The target registration error (TRE) of the higher accuracy primary registration was TREprimary = 31 ± 12 μm. The error in the lower accuracy combined registration was TREcombined = 139 ± 63 μm. Both registration modes are therefore suitable for small‐animal needle interventions. The targeting accuracy of the robotic system was characterized using targeting experiments in tissue‐mimicking gelatin phantoms. The results of the targeting experiments were combined with the known calibration and needle deflection errors to provide a more meaningful measure of the needle positioning accuracy of the system. The combined targeting errors of the system were 149 ± 41 μm and 218 ± 38 μm using the primary and combined registrations, respectively. Finally, pilot in vivo experiments were successfully completed to demonstrate the performance of the system in a biomedical application. Conclusions: : The device was able to achieve the desired performance with an error of <200 μm and improved repeatability when compared to other designs. The device expands the capabilities of image‐guided interventions for preclinical biomedical applications.